Improving Ophthalmology Outpatient Services : A consultation on the development of Ophthalmic Clinical Centres in Northern, Southern and South Eastern Local Commissioning Group/Trust areas: Consultation Document & Equality Impact Assessment.: A consultation on the development of Ophthalmic Clinical Centres in Northern, Southern and South Eastern Local Commissioning Group/Trust areas: Consultation Document & Equality Impact Assessment. ([2016]) - Belfast Health and Social Care Trust,
No abstract available